(untitled) (Fiep Bulletin - online, 2014)
The objective of the research was to compare the physic development of Brazilian and Russian with age from 13,5 to 14,5. The sample of the research was composed by 59 Brazilian students (36 male and 23 female) and 67 Russian students (31 male and 36 female), with age from 13,5 to 14,5, by chosen chance. The individuals of the researched sample realized the follow tests: a)Male: 60 meters running, 3,000metres running, long jump, fixed bar; b) Female: 60 meters running, 2,000 meters running, long jump, fixed bar (body in horizontal position). The results of the research showed that: a) male Brazilian students researched, on average, are significant better ( = 12%, p < 0,05) in physical capacity speed (60 meters running), and female Brazilian students researched in long jump, on average, are significant worst ( = 19%; p < 0,05) than Russian students with the same sex and age. The differences found in the result of other tests do not have confidence (p > 0,05); b) by system of evaluation at physical education subject of Russia School, Brazilian students gained 41,7% (male) and 20,6% (female) great grades and only 5,4% (male) and 2,8% (female) of Russian students gained these grades, but none Russian student gained insufficient grade and 25% of female students and 13,2% of Brazilian students gained these grades. Conclusion: the organization of physic education in Russia school favor to the development all the students of the school and the organization of physic education at Brazilian school favor only the development of those students more gifted physically.